Reproductive biology of sailfin molly, Poecilia latipinna (Lesueur, 1821) in tambak Bosowa Kabupaten Maros - Andi Tamsil; Hasnidar Hasnidar (Jurnal Iktiologi Indonesia, 2019)
Sailfin molly, Poecilia latipinna is one of the alien ornamental fishes in Indonesia. This fish has been found in the aquaculture area in Maros Regency, south Sulawesi as a pest. The research aimed to identify species and observe aspects of reproductive biology of sailfin molly. The study was conducted in the Bosowa Isuma aquaculture area, in Maros Regency from November 2017 to April 2018. Fish was captured using a gillnet. The catches were separated for fish identifying and reproductive biology purposes. For the observation of reproductive biology, the samples were separated by sex according to external morphology. Measurement of total length and weight using calliper (mm) and analytical scales (g), respectively. The gonads preserved in the 4% formalin solution, used for determination of gonad developmental stages and fecundity. Identification results showed that the molly fish found in the ponds was Poecilia latipinna (Lesueur 1821). The length distribution of male and female fish was 26-76 and 31-66 mm with a mean of 51 and 46 mm, respectively. Overall, sex ratio and mature gonads between male and female fish were 1: 2 and 1:10; the growth patterns of male and female were negative allometrics and isometric, respectively. This fish is spawn throughout the year with the peak of spawning in January. The number of larvae to be born (larval fecundity) ranges from 12-111 individuals with an average of ± 32 larva/female. Abstrak Ikan molly, Poecilia latipinna adalah salah satu ikan hias asing di Indonesia. Ikan ini telah ditemukan masuk di areal pertambakan di Kabupaten Maros Sulawesi Selatan sebagai hama. Penelitian bertujuan untuk mengidentifikasi spesies dan mengamati aspek biologi reproduksinya. Penelitian berlangsung dari November 2017-April 2018 di areal pertambakan Bosowa Isuma Kabupaten Maros. Pengambilan sampel menggunakan jaring insang. Sampel dipisahkan untuk tujuan identifikasi dan pengamatan biologi reproduksinya. Untuk pengamatan biologi reproduksi sampel dipi-sahkan berdasarkan jenis kelamin dengan mengamati morfologi tubuh. Pengukuran panjang total menggunakan mis-tar geser dan penimbangan bobot dengan timbangan analitik. Gonad diawetkan dalam larutan formalin 4% digunakan untuk penentuan tingkat kematangan gonad dan fekunditas. Hasil identifikasi menunjukkan bahwa ikan molly yang ditemukan adalah jenis Poecilia latipinna (Lesueur 1821). Sebaran ukuran panjang ikan jantan dan betina adalah 26-76 dan 31-66 mm dengan rataan 51 dan 46 mm. Nisbah kelamin secara keseluruhan dan yang matang gonad (TKG IV) antara ikan jantan dan betina adalah 1 : 2 dan 1 : 10; pola pertumbuhan jantan dan betina adalah allometrik negatif dan isometrik; memijah sepanjang tahun dengan puncak pemijahan pada bulan Januari. Jumlah larva yang akan dila-hirkan (larval fecundity) berkisar 12-111 ekor dengan rata-rata ± 32 ekor larva/induk.